Performance and the City: Constructing Urban Identities in Contemporary London - Di Michele, Laura (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2013)
The relationship between spectators, performers and spaces is investigated in a critical perspective which aims at further developing the concept of the city as a performance place where precarious urban identities are dynamically and temporarily shaped and reshaped. Even if this essay takes into due account the seminal studies of Barthes (1971), H. Lefebvre (1974), and urban theorists such as Reyner Banham and Kevin Lynch who conceived of the city as a ‘legible’ text, at the same time it argues that textuality and performativity must be perceived as intertwined cultural practices that work together to shape the body of phenomenal, intellectual, psychic, and social encounters that frame a subject’s experience of the city. London 2012 Olympic Games, and in particular the stunning Opening Ceremony directed by Danny Boyle, for which visitors and overseas spectators were invited to transform themselves into a global theatrical audience, can be used as a privileged viewpoint from which to analyse the different ways of perceiving, but also being looked at and performing oneself, in and through spaces which tend at modifying, or at interrogating or destabilizing one’s traditional identity.